An ultra-thin, flexible, low-cost and scalable gas diffusion layer composed of carbon nanotubes for high-performance fuel cells. Issue 12 (10th March 2020) - Wei, Jun; Ning, Fandi; Bai, Chuang; Zhang, Ting; Lu, Guanbin; Wang, Huihui; Li, Yali; Shen, Yangbin; Fu, Xuwei; Li, Qingwen; Jin, Hehua; Zhou, Xiaochun
Abstract : A gas diffusion layer (GDL) is one of the essential components of a membrane electrode assembly (MEA), which is the core of proton exchange membrane fuel cells (PEMFCs). Abstract : A gas diffusion layer (GDL) is one of the essential components of a membrane electrode assembly (MEA), which is the core of proton exchange membrane fuel cells (PEMFCs). However, with the rapid development of PEMFCs, current commercial GDLs are encountering or will encounter many problems, such as complex preparation processes, very high preparation temperature (2000 °C), very high thickness, and high cost. In this research, we developed a simple three-step method to produce a novel flexible, low thickness, low-cost, and high performance GDL by a simple process with low preparation temperatures, low energy consumption and low equipment cost. The three-step method mainly includes creating pores, coating with a microporous layer and heat treatment; it uses only carbon nanotube (CNT) films, CNT powder and polytetrafluoroethylene (PTFE) as the raw materials. The temperature of heat treatment in this research is only 350 °C, which is much lower than 2000 °C required for the preparation of commercial GDLs. The new GDL has many advantages, such as very low thickness (less than 40 μm, only about 1/6 of that of commercial GDL), high flexibility (bending radius < 0.17 mm), low cost and large size (200 mm × 200 mm). Moreover, the overall thickness of the MEA prepared with the new GDL was less than 90 μm, which was only about 1/3 of that of the MEA made with a commercial GDL. Outstandingly, the volume-specific power density of the air-breathing PEMFC made with the new GDL dramatically increased to 15 600 W L −1, and the weight-specific power density reached 9660 W kg −1 . It is estimated that the volume-specific power density of the PEMFC stack has potential to be improved by more than 60% by simply replacing the commercial GDL with the new GDL reported in this work. Therefore, this work not only develops a new method for GDL preparation but also provides a new GDL with comprehensive advantages, which is necessary for the next generation of PEMFCs.